A Progressive Approach to Corruption Law Enforcement by the Corruption Eradication Commission in Indonesia - Yasser, Fadli; Wulan, Retno; Pualillin, Azriel (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
This article critically evaluates the extent to which the Corruption Eradication Commission (KPK) of Indonesia continues to embody progressive law principles in corruption enforcement following the controversial 2019 revision of its founding law. Employing a juridical-empirical approach within a critical qualitative framework, this study interrogates the interplay between Satjipto Rahardjo’s progressive law theory, KPK’s institutional performance, and actual policy outcomes. While the KPK has historically demonstrated progressive traits through harsh sanctions, integration of anti-money laundering mechanisms, aggressive asset recovery, and revocation of political rights, the 2019 amendments 2024 period reveals a significant regression. Quantitative indicators (declining sting operations, fluctuating asset recovery, and stagnant Corruption Perception Index scores) and qualitative evidence suggest that structural constraints imposed by Law No. 19/2019 have transformed KPK’s “courage to be different” into selective and politically vulnerable enforcement. The article argues that progressive law at the KPK has increasingly become rhetorical rather than substantive, illustrating the limits of progressive legal theory when confronted with deliberate institutional weakening. Findings contribute to the growing critical literature on the political capture of anti-corruption agencies in semi-consolidated democracies.